ХАРАКТЕРИСТИКА РІВНІВ СФОРМОВАНОСТІ САМОКОНТРОЛЮ УЧНІВ (Педагогіка вищої та середньої школи, 2004)
In the article, the description of levels of formed abilities and skills of self-control of pupils in the process of their educational-cognitive activity is considered.